Modern treatment of melanomas: contribution - Herrera, Ricardo; Saad, Eduardo; Apestegui, Carlos; Besuschio, Santiago (Cirugía del Uruguay, 1974)
Eleven patients with malign melanomas were treated during the period 1972-1973. Most of these patients had light skin and blue eyes. Only one was in the underforty group. The best results were those obtained by oncological perfusion. The future of Inmunology and Inmunotherapy is considered.